Neonatal alloimmune thrombocytopenia due to anti-HPA 5a in a HPA-5a homozygous neonate. (December 2020) - Porta, R.; Serrano, P.; Paltrinieri, A.; Ristic, G.; Canals, C.; Lozano, M.
Abstract: The most frequently involved antigen in severe fetal and neonatal alloimmune thrombocytopenia (FNAIT) is the human platelet antigen 1a. Cases of FNAIT caused by HPA-5a antigen are extremely rare, and usually not severe. We report a case of FNAIT caused by anti-HPA antibodies directed to the HPA-5a antigen. The thrombocytopenia was moderate with a minimal platelet count of 36 × 10 9 /L by day 3, and spontaneously resolved by day 10. The pregnancy had been obtained by in vitro fertilization using embryo donation, creating a complete genetic disparity between the HPA 5b5b mother and the HPA 5a5a homozygous neonate. The use of ART with gamete donation can increase the risk and the severity of alloimmune thrombocytopenia and must be considered in new and subsequent pregnancies.